2018
DOI: 10.1080/14650045.2017.1399878
|View full text |Cite
|
Sign up to set email alerts
|

A Cartography of the Unknowable: Technology, Territory and Subterranean Agencies in Israel’s Management of the Gaza Tunnels

Abstract: This article evaluates the potential for agency exercised by the subterranean volume in geopolitical conflict. Joining recent geographical conceptualisations of territory as a volumetric assemblage with calls for an elemental geopolitics, it argues that the density of the underground layer creates a convoluted technopolitical problem that obfuscates the state's means of directly observing, visualising and knowing the topological space of territory. To illustrate this, a methodological approach based on the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Such a turn towards the subterranean conceptualises the sub-surface as an area with distinctive material properties, such as height, depth and shape. In this vein, recent work has revealed that the subterranean area, like other volumes, is never divorced from state and corporate strategies of control, exploitation and exclusion (Barry, 2013; Kama and Kuchler, 2019; Slesinger, 2020). In the natural resource industries for example, corporate and state entities commonly exercise their power over subterranean volumes through volumetric practices (Bridge, 2013; Kama, 2020; Kama and Kuchler, 2019).…”
Section: Volumetric Politics the Subterranean And Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a turn towards the subterranean conceptualises the sub-surface as an area with distinctive material properties, such as height, depth and shape. In this vein, recent work has revealed that the subterranean area, like other volumes, is never divorced from state and corporate strategies of control, exploitation and exclusion (Barry, 2013; Kama and Kuchler, 2019; Slesinger, 2020). In the natural resource industries for example, corporate and state entities commonly exercise their power over subterranean volumes through volumetric practices (Bridge, 2013; Kama, 2020; Kama and Kuchler, 2019).…”
Section: Volumetric Politics the Subterranean And Elementsmentioning
confidence: 99%
“…Drawing inspiration from this conceptualisation of the geopolitics of land subsidence, I argue that, while political actors make efforts to ‘secure the subterranean volume’, the sub-surface elemental materials and human activity ‘collectively generate a more-than-human agency’ (Slesinger, 2020), or what Valdivia (2015) termed subterranean frictions , against the state’s security assemblage. In short, this paper suggests that, although the subterranean area is mapped and rendered intelligible by geoscientific technologies, underground materials are continuously challenging to control.…”
Section: Volumetric Politics the Subterranean And Elementsmentioning
confidence: 99%
“…This overlooks the dependence of states on the subterranean, as Melo Zurita and Monroe (2019: 40) demonstrate in their study of the ‘uncooperative volume’ of the Yucatan Peninsula, Mexico, where the horizontal spread of the Spanish was checked by their lack of vertical access to aquifers. Gormally et al (2018: 73) also conceive territory as a ‘geosocial challenge’ rather than simple extent, in respect to the required administrative capacity for implementing underground carbon storage (see also Slesinger, 2018; Valdivia, 2015). While there has been increasing interest in the geological power of humans signalled by the Anthropocene, it is the ‘radical indifference of geology to human life’ (Yusoff, 2017: 107), its ‘utter matter’ (Macfarlane, 2019: 4) and unfathomable otherness, which is more salient and perturbing, revealing the ‘limits to our ability to “govern” the rhythms and singularities of earth systems’ (Clark, 2017: 229).…”
Section: Territory Intermezzomentioning
confidence: 99%
“…Allied with recent work on material politics (e.g. Barry 2014;Slesinger 2018) and post-humanist political ecologies (e.g. Sundberg 2011;Boyce 2016), therefore, a central analytical starting point to this paper is that neither the material nor the (bio)physical elements that form part of the borderspace should be considered stable foundations upon which (geo)politics takes place.…”
Section: The Border As Assemblagementioning
confidence: 99%